A Survey Using High-Throughput Sequencing Suggests That the Diversity of Cereal and Barley Yellow Dwarf Viruses Is Underestimated - Sõmera, Merike; Massart, Sébastien; Tamisier, Lucie; Sooväli, Pille; Sathees, Kanitha; Kvarnheden, Anders (Frontiers in Microbiology, 2021)
Worldwide, barley/cereal yellow dwarf viruses (YDVs) are the most widespread and damaging group of cereal viruses. In this study, we applied high-throughput sequencing technologies (HTS) to perform a virus survey on symptomatic plants from 47 cereal fields in Estonia. HTS allowed the assembly of complete genome sequences for 22 isolates of CYDV-RPS, BYDV-GAV, BYDV-PAS, BYDV-PAV, and BYDV-OYV. In addition, we assembled a near-complete genome of the putative novel species BYDV-OYV from Swedish samples of meadow fescue. Previously, partial sequencing of the central part of the coat protein (CP) gene indicated that BYDV-OYV represented a putative new species closely related to BYDV-PAV-CN, which currently is recognized as a subtype of BYDV-PAV. Here, we found that whereas the 3’gene block of BYDV-OYV shares closest relationship with that of BYDV-PAV-CN, the 5’gene block of BYDV-OYV shows the closest relationships with that of BYDV-PAS. Recombination detection analysis revealed BYDV-OYV as a parental virus for both. Analysis of complete genome sequence data indicates that both BYDV-OYV and BYDV-PAV-CN meet the species criteria of genus Luteovirus. Besides BYDV phylogeny, and through a systematic in silico analysis of published primers for YDV detection, the study discusses the existing gaps in current diagnostic practices for detection of YDVs, proposes primer pairs based on the most recent genomic information for the detection of 4 YDV species, and underlines the benefits provided by HTS for continuous up-to-date improvement of diagnostic primers. Thanks to the rising number of sequences available in databases, updating diagnostic primers can improve the test specificity, e.g. inclusivity and exclusivity at species levels, and this is needed to survey properly the geographical and host distribution of the different species of the YDV complex and their prevalence in cereal/barley yellow dwarf disease epidemics.